Use of β-cyclodextrin and milk protein-coated activated charcoal for rapid detection of Listeria monocytogenes in leafy greens by PCR without pre-enrichment. (October 2022) - Li, Xiaoran; Zhang, Ruohong; Wang, Chun; Wang, Xiaofang; Yang, Yang; Cui, Shenghui; Guo, Yunchang
Abstract: Listeriosis outbreaks caused by contaminated leafy greens leaf have increased in recent years, which can pose a serious threat to public health. Thus, a rapid, precise, and effective detection method is urgently needed. We reported a novel sample pre-treatment that utilizes β-cyclodextrin and milk protein-coated activated charcoal to remove PCR inhibitors in leafy green matrices and facilitate the recovery of L. monocytogenes, which can be coupled with PCR subsequently. The primers targeting the iap gene of L. monocytogenes were used for testing the specificity with 141 bacterial strains. Artificially contaminated leafy greens (10 0 –10 5  CFU/25 g) that include spinach, lettuce, Lactuca sativa L., cole, and cabbage were tested to determine the sensitivity of the developed method. Natural leafy greens were tested to evaluate the application of the developed method compared with the conventional culture method. The stability (shelf life) of the reagents used in the developed method was determined using reagents stored at −20 °C for 3, 6, and 12 months to evaluate the sensitivity and application of the method. As a result, the specificity of the developed method was 100% and the detection limit was 10 1  CFU/25 g. The total detection time without pre-enrichment was 4 h. The detection rate of L. monocytogenes (spinach 5%, lettuce 3%, cole 1%, Lactuca sativa L. 0%, and cabbage 0%) and the detection rate of viable bacteria (100%) were consistent in both diagnostic methods (the coincidence rate was 100%). Furthermore, the sensitivity and the application of the developed method were not influenced using the reagents stored for 3, 6, and 12 months. The reagents could be used normally after storing at −20 °C for at least 12 months, which proved that these reagents have good stability under freezing conditions. This method for the detection of L. monocytogenes was rapid, sensitive, and specific, and can potentially be used to detect and monitor the target pathogen in leafy greens and to reduce the potential risk of L. monocytogenes for public health. Highlights: β-cyclodextrin and milk protein-coated activated charcoal combined with PCR detection of L. monocytogenes in leafy greens. The detection limit was 10 CFU/25 g and the total detection time without pre-enrichment was 4 h. The developed method is suitable for natural leafy greens.